PLAA/UFD-3 regulates P-bodies through its intrinsic disordered domain - Alakananda Das; Yanping Qiu; Trevor J. Wolf; Ella Brissett; Jaehyoung Cho; Heenam Park; Eugene C. Chen; Tsui-fen Chou; Paul W. Sternberg (Proceedings of the National Academy of Sciences, 2025)
Regulation of proteome homeostasis is crucial for the survival and adaptation to changing environments for all species. In eukaryotes, this process is finely tuned through regulation at the level of transcription, translation, protein modification, and protein degradation. The phospholipase A2 activating protein (PLAA) is present in all eukaryotes and believed to be a key player in ubiquitin-dependent protein sorting and degradation via its interactions with ubiquitin and/or the AAA+ ATPase, valosin-containing protein (VCP/p97). PLAA’s molecular targets and interaction network remain unclear. We used Caenorhabditis elegans and unbiased proteome-scale approaches to investigate neuronal specific interactors of the C. elegans PLAA ortholog UFD-3 (ubiquitin fusion degradation 3), its effect on ubiquitinated proteins, and global protein expression changes in an ufd-3 mutant. We found that PLAA may play a unique role in cytoplasmic messenger ribonucleic acid (mRNA) processing bodies (P-bodies). Using biochemical analysis in vitro and fluorescence imaging in C. elegans , we show that UFD-3 directly interacts with the mRNA decapping complex regulatory subunit DCAP-1. UFD-3's intrinsic disordered region (IDR), which contains conserved amino acid motifs, is important for the recruitment of DCAP-1 to P-bodies. Finally, we show that loss of the IDR does not affect UFD-3's role in sorting ubiquitinated proteins through the multivesicular body pathway. Collectively, our results suggest that UFD-3's role in P-bodies is distinct from its role in the ubiquitin-dependent protein degradation pathway and the IDR is only critical for UFD-3-regulated P-bodies pathways. Thus, PLAA/UFD-3 might regulate the proteome via two distinct pathways: ubiquitinated protein turnover, as well as mRNA regulation through P-bodies.